UNDERSTADING BALANCE NUTRITION OF CHILDREN AGE 5-6 YEARS THROUGH APPLICATION NUTRITION POP-UP BOOK AT RA AL-IMAN BANARAN - Umami, Naviatul; Tasuah, Neneng (BELIA: Early Childhood Education Papers, 2019)
Nutrition is one of the supporting parts in the development and growth of children. Before children like and consume foods that contain balanced nutrition children need to be introduced in advance about balanced nutrition. Early childhood tend to be more enthusiastic about media that are attractive, colorful and can even move, because actually early childhood is a time when children spend most of their time playing. This study has a problem statement, namely whether there is a difference in understanding balanced nutrition of children aged 5-6 years based on the application of the Nutrition Pop-Up Book in RA Al-Iman Banaran, while this study aims to determine the difference in balanced nutrition with book media. that is. This research is quantitative using the Pre-experimental Design with the One Group Pretest-Posttest Design approach. The sample in this study used children aged 5-6 years in RA Al Iman Banaran which numbered 34 children. Data collection techniques used are observation and Likert scale. The method of analysis of this study was assisted by SPSS 16.0. Based on the calculation results using Paired Sample t-Test shows that if the -ttable> tcount> ttable then it is significant, meaning that it can be interpreted that (-2,042> -30,799 or 30,799> 2,042) with Sig. (2-tailed) of 0,000. The conclusion is that there are differences in the level of understanding of children's balanced nutrition through Nutrition Pop-Up Book children aged 5-6 years at RA Al Iman Banaran. The conclusion of the study is that there is an increased understanding through the media. Some suggestions for schools should facilitate books on balanced nutrition to increase children's understanding of balanced nutrition.  Keywords: Understanding Balanced Nutrition of Children,  Nutrition Pop-Up Book